Risky curves: From unobservable utility to observable opportunity sets - Daniel Friedman; Shyam Sunder (University of California, Economics Department, 2011)
Most theories of risky choice postulate that a decision maker maximizes the expectation of a Bernoulli (or utility or similar) function. We tour 60 years of empirical search and conclude that no such functions have yet been found that are useful for out-of-sample prediction. Nor do we find practical applications of Bernoulli functions in major risk-based industries such as finance, insurance and gambling. We sketch an alternative approach to modeling risky choice that focuses on potentially observable opportunities rather than on unobservable Bernoulli functions.
Keywords: C91; C93; D11; D81; G11; G12; G22; L83; 330; expected utility; risk aversion; St. Petersburg Paradox; decisions under uncertainty; option theory